Local spectroscopic evidence for a nodeless magnetic kagome superconductor CeRu2. (30th November 2022) - Mielke III, C; Liu, H; Das, D; Yin, J-X; Deng, L Z; Spring, J; Gupta, R; Medarde, M; Chu, C-W; Khasanov, R; Hasan, Z M; Shi, Y; et al.
Abstract: We report muon spin rotation ( µ SR) experiments on the microscopic properties of superconductivity and magnetism in the kagome superconductor CeRu2 with T c ≃ 5  K. From the measurements of the temperature-dependent magnetic penetration depth λ, the superconducting order parameter exhibits nodeless pairing, which fits best to an anisotropic s -wave gap symmetry. We further show that the T c / λ −2 ratio is comparable to that of unconventional superconductors. Furthermore, the powerful combination of zero-field (ZF)- µ SR and high-field µ SR has been used to uncover magnetic responses across three characteristic temperatures, identified as T 1 ∗ ≃ 110  K, T 2 ∗ ≃ 65  K, and T 3 ∗ ≃ 40  K. Our experiments classify CeRu2 as an exceedingly rare nodeless magnetic kagome superconductor.